A Case for Decentralization in Zimbabwe’s local government system: Challenges and Opportunities - Madzimure, Takudzwa (Archives of Business Research, 2021)
The issue of decentralization in Zimbabwe’s local government system has been topical since the colonial era. In the post-independence epoch the expectation was that the new majority government would address the centralization of governance which was motivated by racial imbalances. However, decentralization was not achieved as local government was not recognized in the Lancaster House Constitution adopted at independence in 1980. For years this allowed the central government to control all the local government structures in the country. The relationship between local governments and the central government became bitter and tense after the formation of a formidable opposition, MDC, which has been controlling most urban local authorities since its formation. The 2013 Constitution has not improved things either as the central government has not been willing to implement the new law to its latter and spirit. In all this it is the citizens who have been bearing the brunt as there has been poor service delivery owing to the bad relationship between the center and local structures. The study found out that if decentralization is fully implemented in Zimbabwe it has the potential of bringing efficient and effective service delivery, citizen participation, democracy and accountability in the local government system. The paper also makes recommendations on what needs to be done to achieve decentralization in the country’s local government system.